Ectopic Calcification and Hypophosphatemic Rickets: Natural History of ENPP1 and ABCC6 Deficiencies. (16th August 2021) - Ferreira, Carlos R; Kintzinger, Kristina; Hackbarth, Mary E; Botschen, Ulrike; Nitschke, Yvonne; Mughal, M Zulf; Baujat, Genevieve; Schnabel, Dirk; Yuen, Eric; Gahl, William A; Gafni, Rachel I; Liu, Qing; et al.
ABSTRACT: Generalized arterial calcification of infancy (GACI) is a rare disorder caused by ENPP1 or ABCC6 variants. GACI is characterized by low pyrophosphate, arterial calcification, and high mortality during the first year of life, but the natural course and possible differences between the causative genes remain unknown. In all, 247 individual records for patients with GACI (from birth to 58.3 years of age) across 19 countries were reviewed. Overall mortality was 54.7% (13.4% in utero or stillborn), with a 50.4% probability of death before the age of 6 months (critical period). Contrary to previous publications, we found that bisphosphonate treatment had no survival benefit based on a start‐time matched analysis and inconclusive results when initiated within 2 weeks of birth. Despite a similar prevalence of GACI phenotypes between ENPP1 and ABCC6 deficiencies, including arterial calcification (77.2% and 89.5%, respectively), organ calcification (65.8% and 84.2%, respectively), and cardiovascular complications (58.4% and 78.9%, respectively), mortality was higher for ENPP1 versus ABCC6 variants (40.5% versus 10.5%, respectively; p  = 0.0157). Higher prevalence of rickets was reported in 70.8% of surviving affected individuals with ENPP1 compared with that of ABCC6 (11.8%; p  = 0.0001). Eleven affected individuals presenting with rickets and without a GACI diagnosis, termed autosomal recessive hypophosphatemic rickets type 2 (ARHR2), all had confirmed ENPP1 variants. Approximately 70% of these patients demonstrated evidence of ectopic calcification or complications similar to those seen in individuals with GACI, which shows that ARHR2 is not a distinct condition from GACI but represents part of the spectrum of ENPP1 deficiency. Overall, this study identified an early mortality risk in GACI patients despite attempts to treat with bisphosphonates, high prevalence of rickets almost exclusive to ENPP1 deficiency, and a spectrum of heterogenous calcification and multiple organ complications with both ENPP1 and ABCC6 variants, which suggests an overlapping pathology. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR). This article has been contributed to by US Government employees and their work is in the public domain in the USA.